Optimization of Memory Capacity through the Granting of Physical Activity Type with Level of Intensity Low and Medium. (March 2017) - Mulyana, A; Suherman, A; Hendrayana, Y; Budiman, I A
Abstract: The purpose of this study was to determine the effect of the type of physical activity with low and medium intensity level of the ability of memory (short and long term memory). Physical activity is provided in the form of physical activity a variety of physical activities that are categorized as serial skill and similar activities that are categorized as skill continuous. The research method uses Experiment with 2×2 factorial design. The samples were junior high school students who are not involved in sports activities in school or in a club. The sampling technique using Two stage/Multistage-Random Sampling. These samples included 80 students divided into four groups provided treatments for 30 meetings. The instrument used is the letter test, Word test and Formative test. The results showed that physical activity diverse group in particular that of moderate intensity have average scores better than the other groups. There is an interaction between the type and level of intensity of physical activity on the ability of long-term memory only.